ChemInform Abstract: A Short and Elegant Synthesis of (.+‐.)‐Streptopyrrolidine. Issue 38 (30th August 2013) - Shaameri, Zurina; Ali, Sharifah Hidayah Sharif; Mohamat, Mohd Fazli; Yamin, Bohari M.; Hamzah, Ahmad Sazali
Abstract A short synthesis of the natural (4R, 5R)‐streptopyrrolidine (I) and its unnatural (4S, 5S) enantiomer is described.